Crystal structure of 5-hydroxy-5-propylbarbituric acid - Gelbrich, Thomas (Acta Crystallogr E Crystallogr Commun, 2015)
Molecules of the title compound, C(7)H(10)N(2)O(4), systematic name 5-hydroxy-5-propylpyrimidine-2,4,6(1H,3H,5H)-trione, form a hydrogen-bonded framework which is based on three independent hydrogen bonds, N—H⋯O(carbonyl), N—H⋯O(hydroxy) and O—H⋯O(carbonyl). This framework has the topology of the 5-connected nov net. Each molecule is linked to five other molecules via six hydrogen bonds, and the descriptor of the hydrogen-bonded structure is F6(5)[4(4).6(6)-nov]. The crystal packing is isostructural with that of the previously reported 5-hydroxy-5-ethyl analogue.